Price Algorithms as a Threat to Competition Under the Conditions of Digital Economy: Approaches to Antimonopoly Legislation of BRICS Countries - A. Spiridonova; E. Juchnevicius (BRICS Law Journal, 2020)
The authors examine certain legal problems of antitrust regulation in the digital economy facing the international community, including BRICS member countries. This article focuses on the problems associated with the use of price algorithms by enterprises as a threat factor to competition. The concept of “price algorithm” and the goals of its use by enterprises are analyzed; it is concluded that the use of price algorithms is just one of the tools for conducting economic activity. At the same time, enterprises can pose a threat to competition by using price algorithms as an element of concluding anti-competitive agreements (concerted actions) between enterprises and illegal coordination of their activities. Restriction of competition through the use of price algorithms can harm consumers of goods, works, and services and should be controlled by antitrust authorities. Based on the analysis of the antitrust laws of the BRICS member countries, it is concluded that currently the concept of a “pricing algorithm” is not enshrined in the laws of any of the BRICS member states, however, there are prohibitions on anticompetitive agreements of enterprises and illegal coordination of economic activity. We refute the need to legally enshrine the concept of “price algorithm” in antitrust law. At the same time, it proves that enterprises should be held accountable for the use of the price algorithm as atool to limit competition. The paper proves that within the framework of interstate cooperation of the BRICS countries in the field of competition law, it is necessary to develop common approaches to antitrust regulation in the digital economy, including to ensure auniform approach to regulating and controlling the use of price algorithms by enterprises in the framework of economic activity.